IMPLEMENTASI HUKUM HUMANITER INTERNASIONAL DALAM KONFLIK BERSENJATA NON-INTERNASIONAL DI LIBYA - Thareq Nabiel Aziz; Aji Wibowo (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2021)
Non-international armed conflict is a protracted armed conflict involving the government and oneor more armed group but also more less holds the same principle as the international armedconflict, such as the protection of civilians. The arab spring and the fall of Mu’ammar Al-Qadhdhāfīfrom the Libyan Presidency has caused Libya into a downward spiral sparking massive civil warwith many local armed parties that lasted for more than a decade. The armed conflict in Libyacaused many civilian casualties, according to Article 3 Geneva Conventions of 12 August 1949states that in an armed conflict not of an international character the contracting parties mustgive protection to the persons taking no part in the hostilities, members of the armed forces wholaid down their arms to be treated humanely under no circumstances, without any adversedistinction founded on race, color, religion or faith, sex, birth or wealth, or any other similarcriteria . This journal aims to assess the implementation of international humanitarian law in theLibyan non-international armed conflict especially the protection of the civilians, the interferingof international actors in the peace process of Libya, along with explaining the challenges inimplementing international humanitarian law in the context of protection of the civilian. Thenonstop civil war between the Libyan government and the armed group must stop if the Libyanwants peace, they must set aside their difference and talk it out